2019
DOI: 10.1038/s41586-019-1055-0
|View full text |Cite
|
Sign up to set email alerts
|

Observation of fermion-mediated interactions between bosonic atoms

Abstract: In high energy and condensed matter physics, particle exchange plays an essential role in the understanding of long-range interactions. For example, the exchange of massive bosons leads to the Yukawa potential [1,2]. Phonon exchange between electrons gives rise to Cooper pairing in superconductors [3]. When a Bose-Einstein condensate (BEC) of Cs is embedded in a degenerate Fermi gas of Li, we show that interspecies interactions can give rise to an effective trapping potential, damping, and attractive boson-bos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 31 publications
6
102
0
Order By: Relevance
“…When using our measured values for a bf 2 −a bf 1 and a previously known value for a bf 1 = −185± 7 a 0 (40) we calculate the expected mediated interaction shift and find ξ = 1.32 ± 0.18 stat ± 0.35 sys , in good agreement with ξ = 1 theory (18) and a recent mechanical measurement (13).…”
Section: Rkky Mediated Interactions Can Be Intuitively Understood a supporting
confidence: 87%
“…When using our measured values for a bf 2 −a bf 1 and a previously known value for a bf 1 = −185± 7 a 0 (40) we calculate the expected mediated interaction shift and find ξ = 1.32 ± 0.18 stat ± 0.35 sys , in good agreement with ξ = 1 theory (18) and a recent mechanical measurement (13).…”
Section: Rkky Mediated Interactions Can Be Intuitively Understood a supporting
confidence: 87%
“…Clearly, as figure 5 suggests, going to larger samples the solutions change their character from the soliton-like (black solid and dashed lines, left corner) reported by us already some time ago [35] to the one with fully developed flat part typical for droplets (green solid and dashed lines). Noticeably, appearance of a train of Bose-Fermi solitons for appropriately tuned Bose-Fermi interaction, as claimed in [35], has been confirmed in recent experiment [36]. In 1D the fermions can be considered as impurities-much smaller in fraction in comparison to 2D and 3D [13] cases, yet essential for the droplet formation.…”
Section: D Mixturesupporting
confidence: 53%
“…These results are compared to the results we demonstrated in the previous section, which were achieved within the hydrodynamic description of the Bose-Fermi mixture. The atomic-orbital approach has been used by us previously to study the dynamics of Bose-Fermi solitons in quasi-one-dimensional mixtures [25,27] (observed experimentally in [26]) as well as fermionic mixtures, in particular in the context of formation of Cooper pairs [46].…”
Section: Finite System Analysis -Atomic-orbital Approachmentioning
confidence: 99%